Bienestar agresion peer and psychological among students of a public university of Lima - Velásquez Centeno, Carlos (2014)
This research examines the relationships between peer aggression (bullying) and psychological well-being in students from different professional areas of San Marcos University: Health Sciences, Humanities, Social Sciences, Basic Sciences, Engineering and Economic Enterprise. To do this, Scale Peer Violence relates to Espelage (attitude toward violence, prosocial behavior, aggressive behavior and cyberbullying) with Scale of Ryff Psychological Well-Being (positive relationships, autonomy, mastery of environment, personal growth and purpose in life). The study is descriptive-correlational, using an non-probability sampling of the population considered. Instruments mentioned were psychometrically analyzed to fit our reality. As a result it was found that supportive behaviors are linked to the acceptance of itself, use skills and clarity of personal goals; on the contrary, the favorable attitude toward aggressive behavior is associated with low self-acceptance and the mismanagement of the opportunities offered by the environment. Finally, differences were found in age, gender and professional areas.